2020
DOI: 10.3390/e22030354
|View full text |Cite
|
Sign up to set email alerts
|

Radiative MHD Nanofluid Flow over a Moving Thin Needle with Entropy Generation in a Porous Medium with Dust Particles and Hall Current

Abstract: This paper investigated the behavior of the two-dimensional magnetohydrodynamics (MHD) nanofluid flow of water-based suspended carbon nanotubes (CNTs) with entropy generation and nonlinear thermal radiation in a Darcy-Forchheimer porous medium over a moving horizontal thin needle. The study also incorporated the effects of Hall current, magnetohydrodynamics, and viscous dissipation on dust particles. The said flow model was described using high order partial differential equations. An appropriate set of transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 46 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…The numerical solution of the flow of magnetized partially ionized fluid with an amalgamation of nano-sized particles considering the effects of non-uniform heat source, thermal radiations, and heterogeneous homogeneous reactions, is investigated by Nawaz et al 39 . Some recent studies highlighting the impacts of Hall current may be found in [40][41][42][43][44] .…”
Section: Impact Of Hall and Ion Slip In A Thermally Stratified Nanoflmentioning
confidence: 99%
“…The numerical solution of the flow of magnetized partially ionized fluid with an amalgamation of nano-sized particles considering the effects of non-uniform heat source, thermal radiations, and heterogeneous homogeneous reactions, is investigated by Nawaz et al 39 . Some recent studies highlighting the impacts of Hall current may be found in [40][41][42][43][44] .…”
Section: Impact Of Hall and Ion Slip In A Thermally Stratified Nanoflmentioning
confidence: 99%
“…Latest developments in flow through a porous medium with constant porosity and permeability and can be cited through refs. [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However little information is available for variable characteristics of porous space [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]…”
Section: Introductionmentioning
confidence: 99%
“…A nanofluid with magnetic physiognomies is termed as magnetic nanofluid with vast range applications including optical modulators and switches. A good number of magneto-nanofluids explorations may be found in the literature 44 – 46 .…”
Section: Introductionmentioning
confidence: 99%